2006
DOI: 10.1111/j.1469-1809.2006.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

OCA1 in Different Ethnic Groups of India is Primarily Due to Founder Mutations in the Tyrosinase Gene

Abstract: SummaryOculocutaneous albinism (OCA) is a heterogeneous group of autosomal recessive disorders characterized by an abnormally low amount of melanin in the eyes, skin and hair, and associated with common developmental abnormalities of the eye. Defects in the tyrosinase gene (TYR) cause a common type of OCA, known as oculocutaneous albinism type 1 (OCA1). The molecular basis of OCA has been studied extensively in different population groups, but very little information is available on Indian patients. Our invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 14 publications
4
36
0
2
Order By: Relevance
“…According to our current knowledge, 10–25% of the isolated and syndromic OCA cases are not explained by paired, trans-oriented mutations in known genes [34, 35]. Based on our results and the results of previous studies [22], we suggest that screening non-Mendelian OCA-associated genes might elucidate the causative genetic variant for these cases.…”
Section: Discussionsupporting
confidence: 63%
“…According to our current knowledge, 10–25% of the isolated and syndromic OCA cases are not explained by paired, trans-oriented mutations in known genes [34, 35]. Based on our results and the results of previous studies [22], we suggest that screening non-Mendelian OCA-associated genes might elucidate the causative genetic variant for these cases.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, the p.R299H mutation of TYR ranks as the most frequent allele in Chinese (Table 2), Caucasians (Tripathi et al, 1992), Koreans (Park et al, 1997), and Christian Arabs (Zahed et al, 2005), suggesting that it is a common mutational allele in human OCA1. Both the c.929insC and p.R278X alleles in TYR have been reported in some Asian populations (Tripathi et al, 1993;Park et al, 1997;Tomita, 2000;Chaki et al, 2005a). Several mutations of TYR with higher allelic frequencies, such as p.W400L (Lin et al, 2006), c.232insGGG (Tsai et al, 1999), and p.C24Y (Wang et al, 2009a), have to date been reported only in Chinese OCA patients.…”
Section: Discussionmentioning
confidence: 93%
“…Las mutaciones G47D y 1379delTT han sido reportadas en diferentes lugares del mundo y ambas son responsables de albinismo óculo-cutáneo 1A, bien sea en forma homocigota o heterocigota compuesta. La mutación G47D se ha reportado en población de judíos marroquíes y sefarditas (26), en las Islas Canarias y Puerto Rico (24), México, Cuba y en caucásicos de origen no hispano residentes en Estados Unidos (8,27,28), mientras que la mutación 1379delTT ha sido únicamente reportada en población bengalí occidental en la India (21,22).…”
Section: Discussionunclassified